Pemberian Hak Hadanah Kepada Ibu Tiri dalam Putusan Pengadilan Agama Sidoarjo Nomor: 0763/Pdt.G/2018/Pa.Sda Perspektif Maslahah Mursalah - Wafda Firyal (State Islamic University (UIN) of Sunan Ampel, 2019)
This article is a library research on the granting of rights to stepmothers in the decision of the Sidoarjo Religious Court Number: 0763/Pdt.G/2018/PA.Sda. The research data are collected using documentation techniques and are analysed using descriptive analysis techniques and using a deductive mindset that is by outlining the decision of the Sidoarjo Religious Court which is then reviewed from the perspective of maslahah mursalah. The panel of judges in determining the right of gift to stepmothers in the Sidoarjo Religious Court's decision, based on article 41 letter (a) of Law Number 1 of 1974 jo. article 105 and article 156 letter (a) Compilation of Islamic Law and the proposition in the book Bajuri juz II. In addition, a willingness from the Defendant who is the biological father of the child to give the right of gift to the Plaintiff's Reconstruction is a point that is included as consideration by the panel of judges. In Islamic law which is examined from the theory of maslahah mursalah, the judge's consideration to establish the right of hadanah to the stepmother in the Sidoarjo Religious Court's ruling is in accordance with the purpose of the hadanah namely to prioritize the interests and benefit of the child so that later he or she can grow into a good person under the care of an appropriate person, even though the child is not a biological child of the Reconvention Plaintiff, the Reconvention Plaintiff is in fact more feasible and competent to have the right of hadanah.